2017
DOI: 10.1186/s13223-017-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of intelectin-1 in bronchial epithelial cells of asthma is correlated with T-helper 2 (Type-2) related parameters and its function

Abstract: BackgroundIntelectin-1 (ITLN-1) is secreted by intestinal goblet cells and detectable in blood. Its expression is increased in IL-13-overexpressing mouse airways. However, its expression and function in human airways is poorly understood.MethodsDistal and proximal bronchial epithelial cells (BECs) were isolated from bronchoscopic brushings of disease control (D-CON), COPD, inhaled corticosteroid-treated asthma (ST-Asthma) and inhaled corticosteroid-naïve asthma (SN-Asthma) patients. ITLN-1 mRNA expression in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The expression levels of iNOS mRNA in ACs and total BAL cells were determined by quantitative real‐time PCR (qRT‐PCR) as described previously . First‐strand cDNA was synthesized by PrimeScript RT Reagent Kit (Takara Bio, Shiga, Japan) with both oligo(dT) primer and random hexamers.…”
Section: Methodsmentioning
confidence: 99%
“…The expression levels of iNOS mRNA in ACs and total BAL cells were determined by quantitative real‐time PCR (qRT‐PCR) as described previously . First‐strand cDNA was synthesized by PrimeScript RT Reagent Kit (Takara Bio, Shiga, Japan) with both oligo(dT) primer and random hexamers.…”
Section: Methodsmentioning
confidence: 99%
“…ITLN-1 provides protection via directly binding to the S. pneumoniae and representing them to phagocytes for phagocytosis ( Figure 2B ) ( 80 , 87 ). The BECs express ITLN-1 and may also clear the S. pneumoniae via phagocytosis ( 88 90 ).…”
Section: Pulmonary Innate Immune Response During Bacterial Pneumoniamentioning
confidence: 99%
“…COPD develops as a significant and chronic inflammatory response to inhaled irritants. It has been found that clotting proteins of bronchial epithelial cells are involved in the pathogenesis of asthma by regulating CXCL10 expression [ 21 ]. Tyrosine kinase inhibitors can directly inhibit the secretion of CXCL10 in human airway epithelial cells, thereby preventing glucocorticoid-resistant diseases, including COPD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%